Nas Trilhas de Schiller e Kant: Beleza e Moral, uma síntese antropológica - Bezerra, Ralphe Alves (2018)
Since the greek philosophy to the present day, the unilateral anthropological conception has prevailed that privileges rationality to the detriment physical, sensitive and emotional nature. In this theoretical horizon, this research starts from the hypothesis that Schiller's aesthetic philosophy assumes completely a original position on this question, which remains as the most fundamental question of Philosophy, that is, what is man? In this sense, this work has as démarche the fact that Schiller constitutes, as Hegel recognizes, a new concept of Ideal Art as a solution to the main problem of his time, as known, the realization of "true political Freedom". However, it draws attention to the fact that the Schiller’s concepts of Art and Beauty (Schönheit) seem to be methodologically deduced from the nature of an ideal artistic Genius, which, in turn, also refers to the concept of Ideal Humanity. Moreover, this research raises the hypothesis that the Beauty, for having assumed the role of a transcendental moral principle, reveals that Art, rather than representing a mere and "pure instrument" for political education (politische Erziehung), serves Schiller for the foundation of a new anthropology. In this sense, this research also proposes the task of understanding the anthropological-moral content that Art assumes in Schiller's aesthetics. In other words, this investigation intends to discover what allowed the philosopher to convert the Beauty into a "regulative principle." With this purpose, it starts from the assumption that the transcendental thesis of the "conflicts of the antinomies of pure reason", as well as the methodological strategy used to solve them, provide the evidence of an unprecedented path that Schiller walked from the trails opened by the old Kant with his Kritik der reinen Vernunft.